CURAH HUJAN DAN SUHU UDARA TERHADAP KEJADIAN MALARIA DI KOTA BENGKULU - Susilo Wulan; Dirhan Dirhan; Ade Stepani Sudiyanto; Dini Syavani (Kampurui Jurnal Kesehatan Masyarakat, 2022)
High and low incidence of malaria can be controlled by physical environmental conditions of the breeding of Anopheles mosquitoes. Data malaria cases in Bengkulu City for the last 8 years were 1.545, 934, 310, 144, 145, 25, 12 and 3 cases. The biggest factor affected  mosquito breeding is climate. The purpose of  study analyzed  the effects of rainfall, temperature against the incidence of malaria in Bengkulu City. An ecological study using data from Dinkes and BMKG. The dependent variable is malaria incidence and independent variable was rainfall and temperature. Data analysis using univariate, bivariate and multivariate. The result of malaria incidence from 2012-2015 was 1,439 cases with rainfall 108-405 mm and temperature range between 25.57-26.740C. Normality test showed that the three normal distributed variables, Pearson correlation test between rainfall and malaria incidence there is a significant relationship, while the temperature and incidence of malaria there is no significant relationship. Multivariate analysis showed a weak relationship between rainfall and malaria incidence (r = - 0.173). The value of chi square coefficient (R2 = 0.3) means that the regression line equation describes 30% of the variation of malaria occurrence that is affected by rainfall. Suggestions for the results of this study can be to solve the strategy in combating malaria by anticipating if there is a sudden climate change that causes the high number of mosquito breeding and expected community participate in the prevention of malaria disease by maintaining the cleanliness of 3M environment especially in the rainy month.